Human immunodeficiency virus, AIDS, and drug consumption in South America and the Caribbean : epidemiological evidence and initiatives to curb the epidemic - Hacker, Mariana A....[et al.] (2005)
Reviews data on drug use in relation to the spread of human immunodeficiency virus and AIDS in South America and the Caribbean.